Pervasive Blindness and ocular morbidity in the Chepang people of Nepal - Pokharel, Amrit; Kandel, Himal; Shrestha, Priyanka (Nepalese Journal of Ophthalmology, 2017)
Blindness, which is a major burden on the individual and the society, was observed to be pervasively present in a region inhabited by an undermined, disadvantaged ethnic people, the Chepang (Köberlein et al., 2013). Such a plight heralds escalating, already- fragile eye health care in the remote region of Nepal (Ghimire, 2015).